2018
DOI: 10.1002/jat.3693
|View full text |Cite
|
Sign up to set email alerts
|

Specific alteration of gene expression profile in rats by treatment with thyroid toxicants that inhibit thyroid hormone synthesis

Abstract: Transcriptomics technologies have been used for risk assessment of chemicals, mainly to predict the modes of action (MOAs) of chemicals or identify biomarkers. Transcriptomics data may also be helpful to understand MOAs of chemicals at the molecular level in more detail. As an example of the known MOAs, there are two MOAs of thyroid toxicity: inhibition of thyroid hormone synthesis ("direct" effect) and hypermetabolism of thyroid hormone by enzyme induction in liver ("indirect" effect). In the present study, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Epidemiological studies have suggested that environmental exposures to traditional BFRs contribute to human health risk on thyroid homeostasis and functions. Both short-term or chronic exposure to PBDEs (some are structurally analogous to endogenous thyroid hormones, THs) disrupted the thyroid hormone system and thyroid gland histomorphology in rodents. , Various PBDE replacements introduced into commercial markets have been focused on body burden and adverse thyroid outcomes and potential mode of action. , In vivo and in vitro studies on NBFRs including decabromodiphenyl ethane (DBDPE), bis­(2-ethylhexyl) tetrabromophthalate (TBPH), and 2-ethylhexyl-2,3,4,5-tetrabromobenzoate (EH-TBB) exhibited TH homeostasis disruption that is regulated by target transcripts and enzymatic activity of hypothalamic-pituitary-thyroid (HPT) axis in vertebrates, interference with thyroid receptor (TR), and TR-mediated signaling. TRβ active isoform predominantly mediates circulating THs, and its interactions with chemicals including BFRs are a critical initial step that may result in disturbed TH levels and actions. Many thyroid disruptors were reported to competitively bind TR with endogenous THs, resulting in the initiation of alteration on transcriptome and thyroid-responsive phenotypic signature. , PBEB possesses a brominated aromatic ring, a structural scaffold similar to most BFRs; however, whether PBEB might induce TR disruption and thyrotoxic outcomes still remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have suggested that environmental exposures to traditional BFRs contribute to human health risk on thyroid homeostasis and functions. Both short-term or chronic exposure to PBDEs (some are structurally analogous to endogenous thyroid hormones, THs) disrupted the thyroid hormone system and thyroid gland histomorphology in rodents. , Various PBDE replacements introduced into commercial markets have been focused on body burden and adverse thyroid outcomes and potential mode of action. , In vivo and in vitro studies on NBFRs including decabromodiphenyl ethane (DBDPE), bis­(2-ethylhexyl) tetrabromophthalate (TBPH), and 2-ethylhexyl-2,3,4,5-tetrabromobenzoate (EH-TBB) exhibited TH homeostasis disruption that is regulated by target transcripts and enzymatic activity of hypothalamic-pituitary-thyroid (HPT) axis in vertebrates, interference with thyroid receptor (TR), and TR-mediated signaling. TRβ active isoform predominantly mediates circulating THs, and its interactions with chemicals including BFRs are a critical initial step that may result in disturbed TH levels and actions. Many thyroid disruptors were reported to competitively bind TR with endogenous THs, resulting in the initiation of alteration on transcriptome and thyroid-responsive phenotypic signature. , PBEB possesses a brominated aromatic ring, a structural scaffold similar to most BFRs; however, whether PBEB might induce TR disruption and thyrotoxic outcomes still remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…27−29 Many thyroid disruptors were reported to competitively bind TR with endogenous THs, resulting in the initiation of alteration on transcriptome and thyroidresponsive phenotypic signature. 30,31 PBEB possesses a brominated aromatic ring, a structural scaffold similar to most BFRs; however, whether PBEB might induce TR disruption and thyrotoxic outcomes still remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the follicular mean cytoplasmic area is well correlated with the expression of 3 genes classically used to study thyroid function, such as Slc5a5, Tg, and Dio1. 30 Slc5a5 is the gene coding for the NIS allowing the entry of iodide from the bloodstream into the cytoplasm and is therefore a key transporter in the synthesis of thyroid hormones. For all the products studied, the expression of this gene is well correlated with the mean cytoplasmic area.…”
Section: Presumed Resultsmentioning
confidence: 99%
“…Indeed, the follicular mean cytoplasmic area is well correlated with the expression of 3 genes classically used to study thyroid function, such as Slc5a5 , Tg , and Dio1 . 30…”
Section: Discussionmentioning
confidence: 99%
“…The liver, along with being a first-pass organ for the oral route of exposure, is also one of the most common tumor sites in bioassays of industrial chemicals and agrochemicals ( Heusinkveld et al , 2020 ; Hill et al , 2017 ). The extensive set of xenobiotic receptors in liver can serve as transcriptional sensors and sentinels of activity of a chemical that may or may not be tumorigenic in rat liver but would be predicted to be tumorigenic in distant tissues, such as the thyroid or gonads ( Foster et al , 2021 ; Klaunig et al , 2003 ; Murphy and Korach, 2006 ; Ohara et al , 2018 ; Sistare et al , 2011 ; Vansell and Klaassen, 2002 ). Liver transcriptomics can inform if a compound with direct or indirect (anti)estrogenic ( Singhal et al , 2009 ; Ståhlberg et al , 2005 ) or (anti)androgenic activity ( Goetz and Dix, 2009 ; Klaunig et al , 2003 ) may cause tumors in sex organs ( Coulson et al , 2003 ).…”
Section: Transcriptomic Biomarkers Predictive Of Tumorigenic Mechanis...mentioning
confidence: 99%